Anti-dendritic diaphragm and preparation method and application of diaphragm
By adding solid lithium functional particles to the first coating of the lithium battery separator, the safety and stability problems caused by lithium dendrites are solved, and higher safety and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510085134.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The growth of lithium dendrites in lithium batteries will lead to a decrease in battery safety and circulation stability, which may cause heat runaway and combustion explosion.
A coating film containing solid lithium functional particles is used as the separator, and the growth of lithium dendrites is inhibited by adding solid lithium functional particles such as titanium dioxide to the first coating of the separator.
Effectively inhibit the production of lithium dendrites, improve the safety and electrochemical performance of lithium batteries, and extend the cycle life of the battery.
Smart Images

Figure CN119890614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to lithium batteries, and in particular to an anti-dendrite diaphragm and a preparation method and use of the diaphragm. Background Art
[0002] Lithium batteries are widely used, for example: small and thin electronic devices such as smart phones, tablet computers, wearable devices, laptops, etc., car batteries for electric vehicles and hybrid vehicles, residential solar power generation, and fuel cell power storage systems. The formation of lithium dendrites is one of the main reasons for the failure of lithium batteries. The presence of lithium dendrites will seriously affect the safety and cycle stability of lithium batteries. The growth of lithium dendrites will cause instability between the electrode and electrolyte interface during the cycle of lithium batteries, destroying the generated solid electrolyte interface (SEI) film. During the growth process, lithium dendrites will continuously consume electrolyte and cause irreversible deposition of metallic lithium, forming dead lithium, resulting in low coulomb efficiency. The formation of lithium dendrites can even pierce the diaphragm and cause internal short circuits in lithium batteries, causing thermal runaway of the battery and triggering combustion and explosion.
[0003] There are many ways to inhibit the formation of lithium dendrites, such as increasing the design margin of negative electrode materials, improving the consistency of the surface density of positive and negative electrodes, using electrolytes containing specific additives, using diaphragms with specific coatings, etc.
[0004] Based on the diaphragm level, the present invention develops a highly active composite diaphragm and its preparation technology, which fundamentally solves the problem of lithium dendrite growth to improve battery safety and electrochemical performance. Summary of the invention
[0005] A novel coating film containing lithium solidifying functional particles is proposed, wherein the lithium solidifying functional particles are one or more of titanium dioxide, tin dioxide, tin powder, zinc powder, silicon dioxide, silicon powder, silicon carbon mixture, and silver carbon mixture. A lithium battery using this coating film as a separator can actively inhibit the generation of lithium dendrites, and the battery can produce better effects when the coating containing lithium solidifying functional particles faces the negative electrode surface.
[0006] Therefore, the present invention is implemented as follows: a separator includes: a base film and a first coating layer, wherein the first coating layer is formed on one side of the base film, and the first coating layer includes particles having a lithium solidification function.
[0007] Preferably, the particles having the lithium-solidifying function include one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon oxide, silicon powder, silicon carbon mixture, and silver carbon mixture.
[0008] Preferably, the first coating further comprises heat-resistant particles.
[0009] Preferably, the first coating further comprises a binder.
[0010] Preferably, the diaphragm further includes: a second coating, the second coating is formed on the other side of the base film, formed on the side of the first coating relative to the base film, or formed between the first coating and the base film, and the second coating includes heat-resistant particles.
[0011] Preferably, the heat-resistant particles include one or more of alumina, boehmite, and barium sulfate.
[0012] Preferably, the second coating further comprises a binder.
[0013] Preferably, the binder includes one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose.
[0014] The present invention is further implemented as follows: a lithium battery comprises: a positive electrode, a negative electrode, and a diaphragm as described above, wherein the diaphragm is located between the positive electrode and the negative electrode.
[0015] Preferably, the first coating layer of the separator faces the negative electrode.
[0016] The present invention is also implemented as follows: a method for preparing a diaphragm, comprising: providing a base film; applying a first coating on one side of the base film, and the first coating comprises particles containing lithium solidification function; and drying the first coating to form a first coating.
[0017] Preferably, the first coating further comprises one or more of heat-resistant particles and a binder.
[0018] Preferably, the first coating further comprises a solvent.
[0019] The present invention is also implemented as follows: a method for preparing a diaphragm, comprising: providing a base film; applying a first coating on one side of the base film, and the first coating includes particles containing solid lithium function; drying the first coating to form a first coating; applying a second coating on the other side of the base film, and the second coating includes heat-resistant particles; and drying the second coating to form a second coating.
[0020] Preferably, the first coating and the second coating both further include one or more of a binder and a solvent.
[0021] The present invention is also implemented as follows: a method for preparing a diaphragm, comprising: providing a base film; applying a first coating on one side of the base film, and the first coating includes particles containing solid lithium function; drying the first coating to form a first coating; applying a second coating on the side of the first coating opposite to the base film, and the second coating includes heat-resistant particles; and drying the second coating to form a second coating.
[0022] Preferably, the first coating and the second coating both further include one or more of a binder and a solvent.
[0023] The present invention is further implemented as follows: a method for preparing a diaphragm, comprising: providing a base film; applying a second coating on one side of the base film, and the second coating includes heat-resistant particles; drying the second coating to form a second coating; applying a first coating on a side of the second coating opposite to the base film, and the first coating includes particles containing lithium solidification function; and drying the first coating to form a first coating.
[0024] Preferably, the first coating and the second coating both further include one or more of a binder and a solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a cross-sectional schematic diagram showing the diaphragm structure of the first embodiment of the present invention;
[0026] Figure 2 is a cross-sectional schematic diagram showing a diaphragm structure according to a second embodiment of the present invention;
[0027] Figure 3 is a cross-sectional schematic diagram showing a diaphragm structure according to a third embodiment of the present invention;
[0028] Figure 4 It is a schematic cross-sectional view showing the diaphragm structure according to the fourth embodiment of the present invention. DETAILED DESCRIPTION
[0029] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] In the present invention, it is found that coating lithium-solidifying functional particles on the diaphragm can delay the growth of lithium dendrites from the source. The principle is:
[0032] 1. Taking titanium dioxide as an example, titanium dioxide can deintercalate lithium ions, and its specific capacity is as high as 335 mAh / g. Using a diaphragm coated with this substance can increase the actual N / P ratio (or CB value), so that the negative electrode material can have more space to accommodate lithium ions;
[0033] 2. Generally, the positive and negative electrode materials will attenuate to some extent after a certain number of battery cycles, that is, there are not enough locations for lithium ions to be deintercalated, and the excess lithium is prone to produce lithium dendrites. The cycling performance of titanium dioxide is inferior to that of the common graphite negative electrode material. After a certain number of cycles, it will form a Li-Ti-O salt rock phase (no longer participate in chemical reactions), consume part of the active lithium, and the remaining active lithium will undergo normal deintercalation reactions, so that lithium dendrites will not be produced. In fact, when the battery is cycled a certain number of times, the positive and negative electrode materials do not have enough active sites to accommodate lithium ion deintercalation. Consuming some lithium ions in the diaphragm coating can inhibit the formation of "lithium dendrites" from the source, while not affecting the performance of the battery.
[0034] Please see Figure 1 , depicts a diaphragm according to the first embodiment of the present invention, which comprises: a base film (1) and a first coating (2). The first coating (2) is formed on one side of the base film (1), and the first coating (2) comprises particles having a lithium-fixing function.
[0035] The base film (1) may include but is not limited to polyolefins, preferably one or more of polyethylene and polypropylene. The thickness of the base film (1) may be but is not limited to 5 μm to 16 μm, preferably 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or 16 μm.
[0036] The particles containing lithium solidification function may include but are not limited to one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon dioxide, silicon powder, silicon carbon mixture, silver carbon mixture. The first coating (2) may further include one or more of heat-resistant particles and binders. Adding heat-resistant particles to the first coating (2) may enhance the mechanical strength of the diaphragm. Moreover, the heat-resistant particles may improve the thermal stability of the diaphragm, reduce the thermal shrinkage rate, increase the ink-splashing temperature, and enhance the safety performance of the battery under high temperature conditions. The heat-resistant particles may also absorb free F in the electrolyte. -, to avoid corrosion of the current collector. The heat-resistant particles may include but are not limited to one or more of alumina, boehmite, and barium sulfate. The binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the first coating (2) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0037] Under the condition that the first coating (2) includes particles containing solid lithium function and heat-resistant particles, the weight ratio between the particles containing solid lithium function and the heat-resistant particles can be but not limited to 1:(0.143 to 7), preferably 1:0.143, 1:0.333, 1:1, 1:3, or 1:7.
[0038] Under the condition that the first coating (2) includes particles containing lithium solidification function and a binder, the weight ratio between the binder and the particles containing lithium solidification function can be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0039] Under the condition that the first coating (2) includes particles containing solid lithium function, heat-resistant particles, and a binder, the weight ratio between the binder, the particles containing solid lithium function, and the heat-resistant particles can be but is not limited to 1: (2.5 to 17.5): (2.5 to 17.5), preferably 1:2.5:17.5, 1:5:15, 1:10:10, 1:15:5, or 1:17.5:2.5.
[0040] When assembled into a lithium battery, the separator of the first embodiment can be arranged between a positive electrode and a negative electrode. The first coating layer (2) of the separator can be, but is not limited to, facing the negative electrode. Compared with facing the positive electrode, facing the negative electrode helps to improve the anti-dendrite effect.
[0041] The following further describes the method for preparing the separator of the first embodiment:
[0042] First, a base film (1) is provided.
[0043] Next, a first coating is applied to one side of the base film (1), and the first coating includes particles having a lithium solidifying function. The coating may be applied by, but is not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The first coating may further include one or more of heat-resistant particles and a binder. The first coating may further include a solvent, and the solvent may include, but is not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0044] Under the condition that the first coating includes particles containing solid lithium function and heat-resistant particles, the weight ratio between the particles containing solid lithium function and the heat-resistant particles can be but not limited to 1:(0.143 to 7), preferably 1:0.143, 1:0.333, 1:1, 1:3, or 1:7.
[0045] Under the condition that the first coating includes particles containing solid lithium function and a binder, the weight ratio between the binder and the particles containing solid lithium function may be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0046] Under the condition that the first coating includes particles containing solid lithium function and a solvent, the weight ratio between the particles containing solid lithium function and the solvent may be but not limited to 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0047] Under the condition that the first coating includes particles containing solid lithium function, heat-resistant particles, and a binder, the weight ratio between the binder, the particles containing solid lithium function, and the heat-resistant particles may be but is not limited to 1:(2.5 to 17.5):(2.5 to 17.5), preferably 1:2.5:17.5, 1:5:15, 1:10:10, 1:15:5, or 1:17.5:2.5.
[0048] Under the condition that the first coating includes particles containing solid lithium function, heat-resistant particles, and a solvent, the weight ratio between the particles containing solid lithium function, the heat-resistant particles, and the solvent may be but is not limited to 1:(0.143 to 7):(1.657 to 11.6), preferably 1:0.143:1.657, 1:0.333:1.933, 1:1:2.9, 1:3:5.8, or 1:7:11.6.
[0049] Under the condition that the first coating includes particles containing solid lithium function, a binder, and a solvent, the weight ratio between the binder, the particles containing solid lithium function, and the solvent may be but not limited to 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0050] Under the condition that the first coating includes particles containing solid lithium function, heat-resistant particles, a binder, and a solvent, the weight ratio between the binder, the particles containing solid lithium function, the heat-resistant particles, and the solvent may be but not limited to 1:(2.5 to 17.5):(2.5 to 17.5):29, preferably 1:2.5:17.5:29, 1:5:15:29, 1:10:10:29, 1:15:5:29, or 1:17.5:2.5:29.
[0051] Finally, the first coating is dried to form a first coating layer (2). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0052] In addition to the first coating including particles containing a lithium-solidifying function, before drying, the particles containing a lithium-solidifying function can be distributed in the first coating toward a side away from the base film (1). The first coating can be placed below the base film (1) by, but is not limited to, inversion.
[0053] Please see Figure 2 , depicting a diaphragm according to a second embodiment of the present invention, comprising: a base film (1), a first coating (2), and a second coating (3). The first coating (2) is formed on one side of the base film (1), and the first coating (2) comprises particles having a lithium solidifying function. The second coating (3) is formed on the other side of the base film (1), and the second coating (3) comprises heat-resistant particles.
[0054] The base film (1) may include but is not limited to polyolefins, preferably one or more of polyethylene and polypropylene. The thickness of the base film (1) may be but is not limited to 5 μm to 16 μm, preferably 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or 16 μm.
[0055] The particles containing the lithium solidification function may include but are not limited to one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon dioxide, silicon powder, silicon carbon mixture, and silver carbon mixture. The first coating (2) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the first coating (2) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0056] Under the condition that the first coating (2) includes particles containing lithium solidification function and a binder, the weight ratio between the binder and the particles containing lithium solidification function can be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0057] Adding heat-resistant particles to the second coating (3) can enhance the mechanical strength of the diaphragm. Moreover, the heat-resistant particles can improve the thermal stability of the diaphragm under high temperature conditions, reduce the thermal shrinkage rate, increase the ink-splashing temperature, and enhance the safety performance of the battery. The heat-resistant particles can also absorb free F in the electrolyte. - , to avoid corrosion of the current collector. The heat-resistant particles may include but are not limited to one or more of alumina, boehmite, and barium sulfate. The second coating (3) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the second coating (3) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0058] When the second coating (3) includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0059] When assembled into a lithium battery, the separator of the second embodiment can be arranged between a positive electrode and a negative electrode. Moreover, the first coating layer (2) of the separator can be, but is not limited to, facing the negative electrode. Compared with facing the positive electrode, facing the negative electrode helps to improve the anti-dendrite effect.
[0060] The following further describes the method for preparing the separator according to the second embodiment:
[0061] First, a base film (1) is provided.
[0062] Next, a first coating is applied to one side of the base film (1), and the first coating includes particles having a lithium solidifying function. The coating may be applied by, but is not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The first coating may further include a binder. The first coating may further include a solvent, and the solvent may include, but is not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0063] Under the condition that the first coating includes particles containing solid lithium function and a binder, the weight ratio between the binder and the particles containing solid lithium function may be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0064] Under the condition that the first coating includes particles containing solid lithium function and a solvent, the weight ratio between the particles containing solid lithium function and the solvent may be but not limited to 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0065] Under the condition that the first coating includes particles containing solid lithium function, a binder, and a solvent, the weight ratio between the binder, the particles containing solid lithium function, and the solvent may be but not limited to 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0066] Then, the first coating is dried to form a first coating (2). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0067] In addition to the first coating including particles containing a lithium-solidifying function, before drying, the particles containing a lithium-solidifying function can be distributed in the first coating toward a side away from the base film (1). The first coating can be placed below the base film (1) by, but is not limited to, inversion.
[0068] Afterwards, a second coating is applied to the other side of the base film (1), and the second coating includes heat-resistant particles. The coating may be applied by, but is not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The second coating may further include a binder. The second coating may further include a solvent, and the solvent may include, but is not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0069] When the second coating includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0070] When the second coating includes heat-resistant particles and a solvent, the weight ratio of the heat-resistant particles to the solvent may be, but is not limited to, 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0071] When the second coating includes heat-resistant particles, a binder, and a solvent, the weight ratio of the binder, the heat-resistant particles, and the solvent may be, but is not limited to, 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0072] Finally, the second coating is dried to form a second coating layer (3). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0073] It should be noted that there is no order restriction for applying the first coating on one side of the base film (1) and drying the first coating to form the first coating (2) and applying the second coating on the other side of the base film (1) and drying the second coating to form the second coating (3); it is understandable that it is feasible to first form the first coating (2) and then form the second coating (3), or to first form the second coating (3) and then form the first coating (2).
[0074] Please see Figure 3, depicting a diaphragm according to a third embodiment of the present invention, comprising: a base film (1), a first coating (2), and a second coating (3). The first coating (2) is formed on one side of the base film (1), and the first coating (2) comprises particles having a lithium solidifying function. The second coating (3) is formed on a side of the first coating (2) opposite to the base film (1), and the second coating (3) comprises heat-resistant particles.
[0075] The base film (1) may include but is not limited to polyolefins, preferably one or more of polyethylene and polypropylene. The thickness of the base film (1) may be but is not limited to 5 μm to 16 μm, preferably 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or 16 μm.
[0076] The particles containing the lithium solidification function may include but are not limited to one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon dioxide, silicon powder, silicon carbon mixture, and silver carbon mixture. The first coating (2) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the first coating (2) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0077] Under the condition that the first coating (2) includes particles containing lithium solidification function and a binder, the weight ratio between the binder and the particles containing lithium solidification function can be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0078] Adding heat-resistant particles to the second coating (3) can enhance the mechanical strength of the diaphragm. Moreover, the heat-resistant particles can improve the thermal stability of the diaphragm under high temperature conditions, reduce the thermal shrinkage rate, increase the ink-splashing temperature, and enhance the safety performance of the battery. The heat-resistant particles can also absorb free F in the electrolyte. - , to avoid corrosion of the current collector. The heat-resistant particles may include but are not limited to one or more of alumina, boehmite, and barium sulfate. The second coating (3) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the second coating (3) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0079] When the second coating (3) includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0080] When assembled into a lithium battery, the separator of the third embodiment can be disposed between a positive electrode and a negative electrode. Moreover, the first coating layer (2) of the separator can be, but is not limited to, facing the negative electrode. Compared with facing the positive electrode, facing the negative electrode helps to improve the anti-dendrite effect.
[0081] The preparation method of the diaphragm of the third embodiment is further described below:
[0082] First, a base film (1) is provided.
[0083] Next, a first coating is applied to one side of the base film (1), and the first coating includes particles having a lithium solidifying function. The coating may be applied by, but is not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The first coating may further include a binder. The first coating may further include a solvent, and the solvent may include, but is not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0084] Under the condition that the first coating includes particles containing solid lithium function and a binder, the weight ratio between the binder and the particles containing solid lithium function may be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0085] Under the condition that the first coating includes particles containing solid lithium function and a solvent, the weight ratio between the particles containing solid lithium function and the solvent may be but not limited to 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0086] Under the condition that the first coating includes particles containing solid lithium function, a binder, and a solvent, the weight ratio between the binder, the particles containing solid lithium function, and the solvent may be but not limited to 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0087] Then, the first coating is dried to form a first coating (2). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0088] In addition to the first coating including particles containing a lithium-solidifying function, before drying, the particles containing a lithium-solidifying function can be distributed in the first coating toward a side away from the base film (1). The first coating can be placed below the base film (1) by, but is not limited to, inversion.
[0089] Afterwards, a second coating is applied to the side of the first coating (2) opposite to the base film (1), and the second coating includes heat-resistant particles. The coating may be applied by, but not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The second coating may further include a binder. The second coating may further include a solvent, and the solvent may include, but not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0090] When the second coating includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0091] When the second coating includes heat-resistant particles and a solvent, the weight ratio of the heat-resistant particles to the solvent may be, but is not limited to, 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0092] When the second coating includes heat-resistant particles, a binder, and a solvent, the weight ratio of the binder, the heat-resistant particles, and the solvent may be, but is not limited to, 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0093] Finally, the second coating is dried to form a second coating layer (3). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0094] Please see Figure 4 , depicting a diaphragm according to a fourth embodiment of the present invention, comprising: a base film (1), a first coating (2), and a second coating (3). The first coating (2) is formed on one side of the base film (1), and the first coating (2) comprises particles having a lithium solidifying function. The second coating (3) is formed between the first coating (2) and the base film (1), and the second coating (3) comprises heat-resistant particles.
[0095] The base film (1) may include but is not limited to polyolefins, preferably one or more of polyethylene and polypropylene. The thickness of the base film (1) may be but is not limited to 5 μm to 16 μm, preferably 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or 16 μm.
[0096] The particles containing the lithium solidification function may include but are not limited to one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon dioxide, silicon powder, silicon carbon mixture, and silver carbon mixture. The first coating (2) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the first coating (2) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0097] Under the condition that the first coating (2) includes particles containing lithium solidification function and a binder, the weight ratio between the binder and the particles containing lithium solidification function can be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0098] Adding heat-resistant particles to the second coating (3) can enhance the mechanical strength of the diaphragm. Moreover, the heat-resistant particles can improve the thermal stability of the diaphragm under high temperature conditions, reduce the thermal shrinkage rate, increase the ink-splashing temperature, and enhance the safety performance of the battery. The heat-resistant particles can also absorb free F in the electrolyte. -, to avoid corrosion of the current collector. The heat-resistant particles may include but are not limited to one or more of alumina, boehmite, and barium sulfate. The second coating (3) may further include a binder, and the binder may include but is not limited to one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose. The thickness of the second coating (3) may be but is not limited to 2 μm to 4 μm, preferably 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.
[0099] When the second coating (3) includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0100] When assembled into a lithium battery, the separator of the fourth embodiment can be disposed between a positive electrode and a negative electrode. Moreover, the first coating layer (2) of the separator can be, but is not limited to, facing the negative electrode. Compared with facing the positive electrode, facing the negative electrode helps to improve the anti-dendrite effect.
[0101] The following further describes the method for preparing the diaphragm of the fourth embodiment:
[0102] First, a base film (1) is provided.
[0103] Next, a second coating is applied to one side of the base film (1), and the second coating includes heat-resistant particles. The coating may be applied by, but is not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The second coating may further include a binder. The second coating may further include a solvent, and the solvent may include, but is not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0104] When the second coating includes heat-resistant particles and a binder, the weight ratio of the binder to the heat-resistant particles may be, but is not limited to, 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0105] When the second coating includes heat-resistant particles and a solvent, the weight ratio of the heat-resistant particles to the solvent may be, but is not limited to, 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0106] When the second coating includes heat-resistant particles, a binder, and a solvent, the weight ratio of the binder, the heat-resistant particles, and the solvent may be, but is not limited to, 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0107] Then, the second coating is dried to form a second coating layer (3). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0108] Afterwards, a first coating is applied to the side of the second coating (3) opposite to the base film (1), and the first coating includes particles having a solid lithium function. The coating may be applied by, but not limited to, one or more of spin coating, dip coating, cast coating, spray coating, bead coating, rod coating, blade coating, and slit coating. The first coating may further include a binder. The first coating may further include a solvent, and the solvent may include, but not limited to, one or more of water, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, ethanol, and isopropanol.
[0109] Under the condition that the first coating includes particles containing solid lithium function and a binder, the weight ratio between the binder and the particles containing solid lithium function may be but is not limited to 1:(2.5 to 17.5), preferably 1:2.5, 1:5, 1:10, 1:15, or 1:17.5.
[0110] Under the condition that the first coating includes particles containing solid lithium function and a solvent, the weight ratio between the particles containing solid lithium function and the solvent may be but not limited to 1:(1.657 to 11.6), preferably 1:1.657, 1:1.933, 1:2.9, 1:5.8, or 1:11.6.
[0111] Under the condition that the first coating includes particles containing solid lithium function, a binder, and a solvent, the weight ratio between the binder, the particles containing solid lithium function, and the solvent may be but not limited to 1:(2.5 to 17.5):29, preferably 1:2.5:29, 1:5:29, 1:10:29, 1:15:29, or 1:17.5:29.
[0112] Finally, the first coating is dried to form a first coating layer (2). Drying may be performed by, but is not limited to, one or more of drying and blowing. The drying temperature may be, but is not limited to, 50°C to 120°C, preferably 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C, and the drying time may be, but is not limited to, 10 min to 100 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min.
[0113] The present invention is illustrated by the following examples:
[0114] Example 1
[0115] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0116] First, 40g of SnO2 particles with solid lithium function, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0117] Example 2
[0118] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0119] First, 30g of SnO2 particles with solid lithium function, 10g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0120] Example 3
[0121] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0122] First, 20g of SnO2 particles with solid lithium function, 20g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0123] Example 4
[0124] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0125] First, 10g of SnO2 particles with solid lithium function, 30g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0126] Example 5
[0127] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0128] First, 5g of SnO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0129] Example 6
[0130] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0131] First, 5g of SnO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the positive electrode side.
[0132] Example 7
[0133] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0134] First, mix 5g of SnO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water, and stir evenly to obtain the first coating. Then, mix 5g of SnO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water, and stir evenly to obtain the second coating. Then, apply the first coating and the second coating to both sides of the polyethylene base film and dry them at 65°C for 10 minutes to form the first coating and the second coating to obtain the diaphragm. During the full battery test, the first coating and the second coating face the negative electrode side and the positive electrode side respectively.
[0135] Example 8
[0136] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0137] First, 5g of SnO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, 40g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the second coating. Then, the first coating and the second coating were applied to both sides of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating and the second coating to obtain the separator. During the full battery test, the first coating and the second coating faced the negative electrode side and the positive electrode side respectively.
[0138] Example 9
[0139] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0140] First, 5g of TiO2 particles with solid lithium function, 35g of heat-resistant alumina particles, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0141] Example 10
[0142] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0143] First, 5g of Sn powder with solid lithium function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0144] Embodiment 11
[0145] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0146] First, 5g of Al powder with solid lithium function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0147] Example 12
[0148] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0149] First, 5g of Zn powder with lithium solid function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0150] Embodiment 13
[0151] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0152] First, 5g of lithium-solidifying silicon oxide, 35g of heat-resistant granular aluminum oxide, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0153] Embodiment 14
[0154] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0155] First, 5g of silicon powder with solid lithium function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0156] Embodiment 15
[0157] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0158] First, 5g of silicon-carbon mixture with solid lithium function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0159] Example 16
[0160] The diaphragm of this embodiment has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0161] First, 5g of silver-carbon mixture with solid lithium function, 35g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the first coating. Then, the first coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form the first coating to obtain the separator. During the full battery test, the first coating faced the negative electrode side.
[0162] Comparative Example 1
[0163] The diaphragm of this comparative example has a base film thickness of 9 μm and a single coating thickness of 2 μm.
[0164] First, 40g of heat-resistant granular alumina, 2g of binder PVDF and 58g of solvent water were mixed and stirred evenly to obtain the second coating. Then, the second coating was applied to one side of the polyethylene base film and dried at 65°C for 10 minutes to form a second coating to obtain a separator. During the full battery test, the coating faced the negative electrode side.
[0165] Comparative Example 2
[0166] The separator of this comparative example is a polyethylene-based film, and its thickness is 9 μm.
[0167] Test Method
[0168] The thermal shrinkage rate is measured by high-temperature baking. The specific test conditions are a temperature of 130°C and a test time of 1 hour. TD and MD represent longitudinal thermal shrinkage and transverse thermal shrinkage, respectively. The larger the thermal shrinkage rate, the worse the thermal shrinkage of the diaphragm.
[0169] The peel strength was measured by an electronic universal testing machine, and the specific test conditions were an effective length of 200 mm and an effective width of 30 mm.
[0170] The air permeability is measured by a Gurley 4320 permeability meter. The specific test method is the time it takes for 100 mL of gas to pass through the diaphragm. The larger the air permeability increment, the worse the air permeability of the diaphragm.
[0171] The closed-cell / membrane rupture temperature was measured using the Q400 thermal mechanical analyzer from TA Company of the United States. The specific test method was to pull the membrane strips cut in the MD and TD directions with a constant force and simultaneously heat the sample chamber at a heating rate of 5°C / min to obtain the closed-cell temperature and membrane rupture temperature.
[0172] The separator was configured with positive and negative electrodes to make a full battery, and the capacity retention rate was recorded after 200 cycles at 1C / 25℃.
[0173] The diaphragm is configured with positive and negative electrodes to make a full battery. After the battery is charged as required (4.2VCC / CV), a 5mm high-temperature resistant steel needle with a needle tip angle of 50 degrees is used to penetrate from the direction perpendicular to the battery plate at a speed of 25±2mm / s. The steel needle stays in the battery for 10 minutes and then is pulled out to observe the phenomenon.
[0174] The composite diaphragm with functional coating is used to regulate the deposition behavior of metallic lithium, protect the metallic lithium negative electrode, and extend the cycle life of the battery. CR2032 Li|Cu batteries are assembled for testing, and Li is regarded as the negative electrode. The short-circuit time of the battery (i.e., the time when the dendrite pierces the diaphragm and connects Li and Cu) is focused on. The capacity and coulomb efficiency of the battery are not considered, and the short-circuit time of the battery is used as the only criterion for evaluating the functional diaphragm. The battery electrolyte is uniformly selected as 1 mol / L LiTFSI containing 2% LiNO3, the solvent is DOL and DME (1:1 Vol%), and the current density is 1C.
[0175] The test results are shown in Table 1. First, compared with Comparative Example 2, Examples 1 to 16 all have lower MD and TD thermal shrinkage rates, which means that the use of particles containing solid lithium function can improve the safety of the battery separator. Secondly, compared with Comparative Examples 1, 2 and Example 1, Examples 4 and 5 have longer short-circuit times, which means that the particles containing solid lithium function and heat-resistant particles mixed in a specific proportion can significantly inhibit the formation of lithium dendrites. Finally, compared with Example 6, Example 5 has a longer short-circuit time, which means that the coating of particles containing solid lithium function is more effective in inhibiting the formation of lithium dendrites when facing the negative electrode.
[0176] Table 1
[0177]
[0178]
[0179] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0180] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A diaphragm, characterized in that: include: A base film and a first coating layer, wherein the first coating layer is formed on one side of the base film and comprises particles having a lithium solidifying function.
2. The diaphragm according to claim 1, characterized in that The particles having the lithium solidification function include one or more of titanium dioxide, tin dioxide, tin powder, aluminum powder, zinc powder, silicon oxide, silicon powder, silicon carbon mixture, and silver carbon mixture.
3. The diaphragm according to claim 1, characterized in that The first coating further includes heat-resistant particles.
4. The diaphragm according to claim 3, characterized in that The first coating further includes a binder.
5. The diaphragm according to claim 1, characterized in that It further includes: a second coating, wherein the second coating is formed on the other side of the base film, formed on the side of the first coating relative to the base film, or formed between the first coating and the base film, and the second coating includes heat-resistant particles.
6. The diaphragm according to claim 3 or 5, characterized in that: The heat-resistant particles include one or more of alumina, boehmite, and barium sulfate.
7. The diaphragm according to claim 5, characterized in that The second coating further includes a binder.
8. The diaphragm according to claim 4 or 7, characterized in that: The binder includes one or more of polytetrafluoroethylene, polytetrafluoroethylene, polypropylene, polyethylene, and sodium hydroxymethylcellulose.
9. A lithium battery, characterized in that: include: A positive electrode, a negative electrode, and a separator according to claim 1, wherein the separator is located between the positive electrode and the negative electrode.
10. The lithium battery according to claim 9, characterized in that: The first coating layer of the separator faces the negative electrode.
11. A method for preparing a diaphragm, characterized in that: include: providing a base film; Applying a first coating on one side of the base film, wherein the first coating includes particles having a lithium-solidifying function; and drying the first coating to form a first coating layer.
12. The method for preparing a diaphragm according to claim 11, characterized in that: The first coating further includes one or more of heat-resistant particles and a binder.
13. The method for preparing a diaphragm according to claim 12, characterized in that: The first coating further includes a solvent.
14. A method for preparing a diaphragm, characterized in that: include: providing a base film; Applying a first coating on one side of the base film, wherein the first coating includes particles having a lithium-solidifying function; drying the first coating to form a first coating layer; A second coating is applied on the other side of the base film, wherein the second coating comprises heat-resistant particles; and the second coating is dried to form a second coating layer.
15. The method for preparing a diaphragm according to claim 14, characterized in that: The first coating and the second coating both further include one or more of a binder and a solvent.
16. A method for preparing a diaphragm, characterized in that: include: providing a base film; Applying a first coating on one side of the base film, wherein the first coating includes particles having a lithium-solidifying function; drying the first coating to form a first coating layer; A second coating is applied on a side of the first coating opposite to the base film, wherein the second coating comprises heat-resistant particles; and the second coating is dried to form a second coating.
17. The method for preparing a diaphragm according to claim 16, characterized in that: The first coating and the second coating both further include one or more of a binder and a solvent.
18. A method for preparing a diaphragm, characterized in that: include: providing a base film; Applying a second coating on one side of the base film, wherein the second coating comprises heat-resistant particles; and drying the second coating to form a second coating layer; A first coating is applied on a side of the second coating opposite to the base film, wherein the first coating comprises particles having a lithium-solidifying function; and the first coating is dried to form a first coating.
19. The method for preparing a diaphragm according to claim 18, characterized in that: The first coating and the second coating both further include one or more of a binder and a solvent.